(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Bekti HS, Budi SW, Wibowo C. 2022. Arbuscular mycorrhizal fungi inoculum and soil ameliorants enhance the growth of Falcataria moluccana in revegetation of post-silica sand mining land in Sukabumi, Indonesia. Biodiversitas 23: 1181-1187. Open-pit mining of silica sand caused several negative impacts on the environment, especially inhibited plant growth. MycoSilvi is Arbuscular Mycorrhizal Fungi (AMF) inoculum enriched with Mycorrhizal Helper Bacteria (MHBs) which could increase plant growth and nutrient uptake in degraded soils. A ?eld experiment was conducted to study the growth response of F. moluccana (Miq.) Barneby & JW Grimes seedlings treated with MycoSilvi inoculation and soil ameliorants (lime and compost) in post-silica sand mining land. The experimental design used in this study was a completely randomized block design with a factorial scheme. The results showed that MycoSilvi inoculation combined with soil ameliorant significantly improved plant growth of F. moluccana and assisted plant survival within nine months after transplantation in the field. MycoSilvi inoculation and soil ameliorants also increased the number of bacteria in the soil rhizosphere compared with control treatment. This study indicated that revegetation with MycoSilvi inoculation and soil ameliorants could influence plant establishment and development of microbial soil communities in infertile soils, suggesting that it could be an effective method for further ecological rehabilitation in degraded land areas.